761. Host Intestinal Defenses Against Clostridioides difficile Infection in Chemotherapy Patients. (4th December 2021) - Weinstein, Claire; Wilkinson, Racheal; Apewokin, Senu
Abstract: Background: Clostridioides difficile infection (CDI) is a common complication in patients undergoing cancer treatment with cytotoxic chemotherapy. Exposure to antibiotics or chemotherapy disrupts the microbiome by killing protective intestinal flora which consequently promotes C. difficile spore germination and disease. The host defense against CDI includes colonization resistance conferred by the healthy microbiome and innate defenses provided by intestinal epithelial cells. One protective factor secreted by Paneth cells of the intestinal epithelium is lysozyme, an enzyme that degrades the cell walls of Gram-positive bacteria such as C. difficile . We hypothesized that chemotherapy-induced mucosal barrier injury and the resultant death of Paneth cells leads to decreased production of lysozyme. We thus sought to examine changes in lysozyme concentration in stools of chemotherapy patients. Methods: We collected stool samples from six patients undergoing cancer treatment at four different time points. The first stool sample corresponded to the day prior to the start of chemotherapy (day zero). We then performed ELISA assays to determine the lysozyme concentration for each stool sample. Results: On day zero, the lysozyme levels (n=6) averaged 268.1 ± 131.7 ng/mL. Over the course of chemotherapy, the lysozyme levels decreased 78.70 ± 24.19% from the starting value. The lowest values were observed around days 5 through 11 for most patients, coinciding with when they were most neutropenic around day 11. One of the patients developed CDI on day 5 and experienced more fluctuating lysozyme levels thereafter. On the day that the patient developed CDI, lysozyme was measured as 6.63 ng/mL. Throughout treatment, 3/6 patients showed recovery of lysozyme production with white blood cell recovery. Conclusion: Our data indicate that chemotherapy causes decreased concentrations of lysozyme in stool. Low lysozyme levels could in part account for the increased susceptibility to CDI during chemotherapy. Future experiments will include bioinformatics analyses to determine how the microbiome changes in response to chemotherapy. Together, these experiments will inform our approach to determining patient susceptibility to chemotherapy-associated CDI. Disclosures: All Authors : No reported disclosures